A spiro-bifluorene based 3D electron acceptor with dicyanovinylene substitution for solution-processed non-fullerene organic solar cells1. Issue 20 (28th May 2015) - Xia, Debin; Gehrig, Dominik; Guo, Xin; Baumgarten, Martin; Laquai, Frédéric; Müllen, Klaus
<x xml:space="preserve">Abstract</x> A 3D acceptor for bulk heterojunction solar cells.